Micro markets : a market structure approach to microeconomic analysis - Schwartz, Robert A. (Robert Alan), 1937- (John Wiley & Sons, 2010)
A timely guide that bridges the gap between microeconomic theory and practice through real-world application in the marketplace. Understanding how microeconomics affects the marketplace is essential for any investment professional, however most books simply address microeconomics in its pure theory-based form. Micro Markets helps bridge the gap between theory and practice by defining microeconomics in terms of real-world, market applications. This timely guide elucidates basic microeconomic concepts with an emphasis on applicability. It establishes a common application for all of the basic eco.